The relationship between currency and stock price in four Asian currencies / Noor Izzatul Liana Mohamed - Mohamed, Noor Izzatul Liana (Faculty of Business and Management, 2010)
As the currency effect on the stock market, it is finds that currency depreciation leads to a decline in the stock prices in the short run. This is explaining that there is negative relationship between exchange rates and stock prices. Exchange rate depreciation suggests higher inflation in the future, which makes investors worried about the future performance of companies. Moreover, depreciation of the currency has great impacts to the investors but the impact may vary due to the different level of economic development. As a result, the stock prices drop. This hypothesis supported by data from UK markets. Stock prices and exchange rates play an important role in influencing the development of economic of a country. The relationships between stock prices and exchange rates have frequently been utilized in forecasting the future trends for each other by fundamentalist investors. In an open economy, the exchange rates play an important role in the movements of the stock price especially for internationally investment. Before economic crisis, Malaysian economy has been growing at an average of 8.5% per year for more than a decade. Accompanying this growing was a rapid acceleration of stock prices. According to the Azman- Saini et al (2006), an excessive amount of short-term capital had led to an overheated stock market and asset prices which lead to the weakness of financial system. The following down of Thai (BATH) in 1997 had triggered a wave of currencies depreciation in the region. In the second half of 1997, the ringgit depreciated by 33.6%against dollar and reached the historic low of MYR 4.88 per dollar on January7, 1998. In order to stabilize the ringgit, selective capital control were introduced on the September 1, 1998 which witnessed the ringgit was pegged at MYR 3.80 per dollar.